Virtual otolaryngologic management of sleep apnea patients: Lessons learned from COVID‐19 pandemic. Issue 3 (5th May 2021) - Huntley, Colin; Boon, Maurits; Ishman, Stacey; Capasso, Robson; Crawford, Julia; D'Agostino, Mark A.; Hoff, Paul
Abstract: Objective: To discuss the virtual management options and strategies learned during the COVID‐19 pandemic for treatment of patients with sleep complaints and sleep disordered breathing presenting to the otolaryngologist. Methods/Results: The addition of a virtual evaluation can be beneficial in assessing the patient presenting to the otolaryngologist with sleep complaints. With the implementation of telemedicine, validated subjective assessment tools, and a limited physical exam, patients can be triaged for the need for treatment implementation, further evaluation or testing, and counseled regarding various management options. In this article, we discuss the lessons learned from the authors' collective experience on how to effectively use telemedicine as a tool in the management repertoire for patients with sleep disorders. Conclusion: The otolaryngologist will commonly see patients with sleep complaints, particularly patients diagnosed with obstructive sleep apnea not able to tolerate conservative therapies. These patients are well suited for virtual evaluation utilizing telemedicine. The technology and workflows which have been developed during the COVID‐19 pandemic can be carried forward for select patients to improve access and efficiency of care. Level of evidence: 5.